Biodiversity for improved nutrition and health: The critical role of food composition in decision making for agriculture and nutrition programming and policy. 11th IFDC Pre-Conference Workshop IV. Hyderabad, India, 2 November 2015. - Bioversity International (Bioversity International, 2015)
Food composition data are an essential yet often underutilized resource to help decision making and planning for nutrition programming and policy decisions. Food composition data could be used much more widely to inform a wide array of stakeholders within multiple sectors including agriculture, health, education and trade. This preconference session will explore how food composition data can be used in nutrition programming as well as for influencing diverse national policies and social protection programmes. It will focus on a wide range of programmatic uses of food composition data, including breeding for nutritional outcomes, selection of locally available foods for national programmes such as school feeding and use of intra-specific diversity to promote resilience and greater opportunities for dietary diversification. Case studies that illustrate diverse uses of food composition data for nutrition programing and policy setting will be presented.